516 Does the Use of Adjuvant Chemotherapy Increase Incisional Hernia Rates in Colorectal Cancer Patients – A Retrospective Single Centre Cohort Study. (12th October 2021) - Singh, N; Gupta, K; Khan, T; Rahman, E; Singh-Ranger, D
Abstract: Aim: Incisional hernias (IH) are a known complication of any major abdominal surgery. It is known that chemotherapy impairs healing processes via delayed inflammation, impaired collagen synthesis and reduced fibrin deposition and wound contraction. There are currently, to our knowledge, no trials examining the effect of adjuvant chemotherapy on incidence of IH in patients with colorectal cancer. This study aims to assess the same by comparing IH rates between chemotherapy and non-chemotherapy patient groups. Method: All the patients who had major surgery for colorectal cancer between January 2009 and January 2014 were divided into two groups of chemotherapy (A) and non-chemotherapy (B). Records of first 160 patients from each group were retrospectively analysed. Results: There were non-significant differences between groups for sex, tumour location, primary operation, and type of procedure (emergency or elective). Significant differences were observed for age (more elder patients in group B, p = 0.000011), method of access (more open procedures in group B and more laparoscopic procedures in group A, p = 0.0007) and Charlson co-morbidity scores (more advanced score in group B, p = 0.029). We found that 21/120 (21.21%) patients in the chemotherapy group and 12/99 (13.79%) patients in non-chemotherapy group developed Incisional hernias. Although there was a higher rate of IH in the chemotherapy group, this was not statistically significant (p = 0.27). Conclusions: Although this study fails to demonstrate any statistically significant difference in IH incidence between two groups, but this study can act as a pilot in order to fuel further high-quality research to draw more valid conclusions.